Можливості взаємодії логіки та риторики в публічних виступах та суперечці - Базарна, П. А. (ХНУРЕ, 2024)
This article explores the interplay between logic and rhetoric in public speaking and debate. The role of rhetoric as the art of persuasive speech and the role of logic in structuring arguments and forming conclusions are considered. The article gives examples from practice and analyzes them, showing how logic and rhetoric interact in real situations. The interaction of logic and rhetoric is a key aspect of an effective communication process
Keywords: риторика; публічні виступи